Improving the Social Skills of Students with ADHD through the Implementation of the Think-Pair-Share Cooperative Learning Strategy at BND Kaubun Kindergarten - Yatin, Sri; Mahabbati, Aini; Ishartiwi, Ishartiwi (FKIP Universitas Wisnuwardhana, 2026)
This study seeks to enhance the social skills of students with ADHD by employing a cooperative learning methodology, namely the think-pair-share model, at BND Kaubun Kindergarten. Although cooperative learning has been widely applied in early childhood education, limited studies have specifically examined its effectiveness in improving the social skills of students with ADHD in kindergarten settings, particularly through the integration of engaging physical-motor activities. This research employed the Kemmis and McTaggart Classroom Action Research framework, consisting of two cycles. The research subject consisted of one student exhibiting ADHD symptoms in Group B. Data collection methods included a social skills attitude evaluation instrument and observational learning assessments. The study employed quantitative methods for the outcomes of the attitude evaluation scale and qualitative methods for observational data. The results indicated a significant enhancement in the social skills of the student with ADHD in Group B at BND Kaubun Kindergarten. This success resulted from the application of the think-pair-share cooperative learning strategy, complemented by engaging physical-motor stringing activities. This implementation positively influenced the student’s ability to respond to questions, take turns speaking, share, cooperate, manage emotions, and demonstrate empathy. The improvement was evidenced by increased scores on the attitude scale, from 28% in the pre-action stage to 44.44% and 66.77% in Cycle I, and further to 86.11% and 94.44% in Cycle II. This progress is attributed to the student’s enthusiasm for collaborative learning and interest in hands-on activities using novel materials. Therefore, this study implies that the integration of structured cooperative learning strategies with interactive physical activities can serve as an effective approach for educators to support the social development of students with ADHD in early childhood education settings.